Pengembangan Modul Keterampilan Menulis pada Mahasiswa Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Baturaja - Agustina, Aryanti; Lestari, Dewi (Lentera: Jurnal Ilmiah Kependidikan, 2020)
The purpose of this research is to develop writing skills module teaching materials. The development model used in this research is the research and development model. The approach taken is mix methods research that combines qualitative and quantitative methods. The development model applied is that proposed by Jolly and Bolitho (in Tomlinson, (1998), Dick, Carey, and Carey (2005) and Tessmer (1998), The researcher collaborates with Dick, Carey, and Carey's model with Tessmer's evaluation model. The Tessmer model has five evaluation stages, namely the following self evaluation, expert reviews, one-to-one, small group and field test. The more often a product is evaluated, the more interesting the results will be, with the collaboration of these two models, it is hoped that it can produce a module that is valid, practical, and effective.